Differences in Heating Temperature and Type of Phytase Enzyme on Enzyme Activity, Calcium and Phosphorus Levels in Complete Poultry Feed - Sobur, Sobur; Tafsin, Makruf; Julianti, Elisa (Jurnal Agripet, 2024)
Phytic acid is an antinutritional factor that can negatively affect livestock productivity by reducing the bioavailability of essential nutrients. Its content in feed ingredients can be minimized or even eliminated through various processing techniques, such as the addition of phytase enzymes. This study aimed to evaluate the effects of different heating temperatures and types of phytase enzymes on enzyme activity, calcium, and phosphorus levels in complete poultry feed. The research was conducted using a completely randomized design (CRD) with a factorial arrangement. The treatment consisted of two factors: factor A (phytase enzyme addition at three levels: no enzyme (0 FTU), commercial enzyme A (800 FTU), and commercial enzyme B (800 FTU), and factor B (heating temperature levels of 65C, 70C, 75C, and 80C). Each treatment combination was replicated three times. Data were analyzed using Minitab software, followed by Duncan's Multiple Range Test (DMRT) to determine significant differences between treatments at a 5% significance level. The results indicated that the addition of phytase enzymes significantly affected (P0.05) enzyme activity, calcium, and phosphorus levels in the feed. The best results for enzyme activity were observed with the treatment EAT3 (commercial phytase enzyme A at a heating temperature of 75C), while the best results for calcium and phosphorus levels were achieved with treatment EBT3 (commercial phytase enzyme B at a heating temperature of 75C).